2007
DOI: 10.1021/ic700544b
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Complexes with New Polypodal Ligands Presenting Axial−Equatorial Phenoxo Bridges {2-[(Bis(2-pyridylmethyl)amino)methyl]-4-methylphenol, 2-[(Bis(2-pyridylmethyl)amino)methyl]-4-methyl-6-(methylthio)phenol}:  Examples of Ferromagnetically Coupled Bi- and Trinuclear Copper(II) Complexes

Abstract: Two new ligands, 2-[(bis(2-pyridylmethyl)amino)methyl]-4-methylphenol (HL) and 2-[(bis(2-pyridylmethyl)amino)methyl]-4-methyl-6-(methylthio)phenol (HSL), were synthesized and were used to prepare the trinuclear copper(II) complex {[CuSL(Cl)]2Cu}(PF6)2.H2O (1) and the corresponding binuclear complexes [Cu2(SL)2](PF6)2 (2) and [Cu2L2](PF6)2 (3). The crystal structure of 1 shows two different coordination environments: two square base pyramidal centers (Cu1 and Cu1a, related by a C2 axes), acting as ligands of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…This superexchange pathway, which does not seem very effective, has been less studied than the equatorial one. In spite of this, there are several examples of this kind of magnetic interaction reported in the literature that indicate that it should promote a small (ferro- [34] or antiferromagnetic [34][35]) or null [36] magnetic exchange. Thus, this is in agreement with the low -2J value found for 1, which does not merit further consideration.…”
Section: Magnetic Studiesmentioning
confidence: 99%
“…This superexchange pathway, which does not seem very effective, has been less studied than the equatorial one. In spite of this, there are several examples of this kind of magnetic interaction reported in the literature that indicate that it should promote a small (ferro- [34] or antiferromagnetic [34][35]) or null [36] magnetic exchange. Thus, this is in agreement with the low -2J value found for 1, which does not merit further consideration.…”
Section: Magnetic Studiesmentioning
confidence: 99%
“…It has also been stated that when the copper centers are connected axially by a bridging phenoxido group, they exhibit very weak ferro-and antiferromagnetic or no interaction. [26][27][28] Thus, in our case, the magnetic exchange is mediated principally through alkoxido bridges. Both theoretical and experimental studies have shown that the major factor controlling the magnetic exchange interaction in dialkoxido-bridged dicopper(II) complexes is the value of the Cu-O-Cu angle and a linear variation of J with θ (the Cu-O-Cu angle).…”
Section: Magnetic Propertiesmentioning
confidence: 78%
“…Therefore, the magnetic exchange coupling mediated by the phenoxido-bridge magnetic pathway should be very small. [26][27][28] In view of this, in a first approach, only the J 1 parameter for the alkoxido-bridge pathway was considered. The χ M T versus T data were simulated through a full-matrix diagonalization method by using the MAGPACK [29] program with the above Hamiltonian and J 2 = 0 cm -1 .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…9-11 Additionally, there is an increasing interest in studying the cyclic trinuclear copper(II) complexes because they can be geometrically frustrated systems which offer the opportunity to examine magnetic exchange models such as spin frustration, spin delocalization, or antisymmetric exchange. and co-workers 17 as DNA nucleases and cytotoxic agents. Complex 3 shows its DNA cleavage activity in absence of any external coreductant.…”
Section: Introductionmentioning
confidence: 99%